Translation and validation of the Manchester Clinical Supervision Scale©: Effective clinical supervision evaluation - Cruz, Sandra (2011)
In Portugal, we are at the beginning of clinical supervision in nursing. We carried out a research to translate and validate the Manchester Clinical Supervision Scale© (MCSS) into Portuguese language from Portugal. Thus, we can assess the clinical supervision process. We applied the methods of translation and back – translation and experts analyzed translations. MCSS and the back translation were compared by collaborative parties. An empirical study using a test – retest design was made to estimate cross-cultural relevance. Cronbach’s alpha value for the total score was 0,923 in both periods. The Portuguese version is culturally acceptable and consistent with the original.